Analysis of successful offensive play patterns by the Spanish soccer team - Amatria, M.; Maneiro, R.; Anguera, M. T. (Journal of Human Kinetics, 2019)
Victory is the ultimate aim in soccer and therefore when a team wins an elite European or world championship, attempts will invariably be made to emulate the winning team 's style of play. In this study, we performed an in-depth analysis of play by the Spanish soccer team during the 2012 UEFA European Championship, where it was crowned champion. Using observational methodology and T-pattern analysis, we identified hidden patterns of play that ended in a goal for the Spanish team. A generalizability coefficient (e2) of 0.986 demonstrated that the offensive patterns detected are robust and highly generalizable. These patterns were formed by technical actions consisting of ball control and pass, with alternations between short and long passes, in the central area of the rival pitch, with use of both wings to achieve width of play and prioritization of width over depth of play. We also found patterns showing that goals and shots at goal were made on a ball delivered from the opposite direction to the shot and were not preceded by a technical action.